Microbiology A Human Perspective. - Nester, Eugene W Roberts, C Evans (WCB McGraw-Hill, 1998)
This introductory microbiology text uses a clear writing style to provide an understanding of microbial diseases. This edition takes an organ systems based approach to human diseases and emphasizes the relevance of microbiological principles to human health.